2004
DOI: 10.1080/01485010490269542
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Reproduction in Hiv and HCV Infected Men of Serodiscordant Couples

Abstract: In serodifferent couples, there is a significant risk of sexual transmission of HIV, while the risk of transmitting HCV is minor. That said, the whole of the ejaculate is not necessarily infected and, therefore, hazardous. A careful dissection of its components by which motile sperm is separated and subsequently analyzed to verify the absence of viral elements could allow these couples a safer access to the reproductive process. The development in the field of assisted reproduction of new laboratory techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In our study, sperm was bacteria-free in both groups before cryopreservation, and the leukocyte count was under the WHO threshold (<1 million/ml). 3-Sperm characteristics were similar in our two groups, as has been previously demonstrated in treated patients and untreated patients [37]. But it has been shown that antiviral drugs reduce sperm progressive motility, especially when reverse transcriptase nucleoside inhibitors are used [21,22].…”
Section: Fragmentation Rate and Viral Infectionsupporting
confidence: 64%
“…In our study, sperm was bacteria-free in both groups before cryopreservation, and the leukocyte count was under the WHO threshold (<1 million/ml). 3-Sperm characteristics were similar in our two groups, as has been previously demonstrated in treated patients and untreated patients [37]. But it has been shown that antiviral drugs reduce sperm progressive motility, especially when reverse transcriptase nucleoside inhibitors are used [21,22].…”
Section: Fragmentation Rate and Viral Infectionsupporting
confidence: 64%
“…In contrast, both recent and earlier studies concluded that purification of motile spermatozoa by either the discontinuous gradient or swim-up method, or even by a combination of these techniques, reduces the number of HIV and/or HCV particles in semen to undetectable levels 8,14,17,18,24,28,32 , making it possible for serodiscordant couples to conceive a child by means of assisted reproduction techniques with minimum risk of seroconversion 14,15,32 .…”
Section: Introductionmentioning
confidence: 80%
“…This would especially be the case in patients with high HCV titer, due to interference in the production of cellular cytokines, causing the HIV/HCV viral load to increase even further 47 . The advent of HAART, however, is also changing the natural history of HIV/HCV coinfection because of increased patient survival 15 . As a result, an ever increasing number of serodiscordant couples wish to have their own child without resorting to gamete donation in sperm banks or giving up safe sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation